Starpol The Star scanner - Tully, John (Ginn and Company Ltd, 1987)
This story book also highlight what took place when the SM4 team took off in their spaceship. then hunter 3 left with jill fox locked up on board,etc.
Keywords: Juvenile literature-Fiction